2021
DOI: 10.1177/10547738211006242
|View full text |Cite
|
Sign up to set email alerts
|

Translation, Adaptation, and Validation of Chronic Kidney Disease Self-Management and Knowledge Instruments for People at Pre-Dialysis Stage in the Arab World

Abstract: Knowledge is critical for self- management, however there are no measures available in Arabic to effectively assess knowledge and self-management for chronic kidney disease (CKD). The aim of this study was to translate, culturally adapt, and validate Chronic Kidney Disease Self-Management Instrument-29 (CKD-SM-29) and Kidney Disease Knowledge survey (KiKs) for use by Arabic-speaking health professionals and patients. The study was carried out in two phases: translation and cultural adaptation, and validation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…The result of test-retest analyses showed that the MCKD-SM was very stable over the 2-week period. Besides, ICC score was higher than the original [9], Vietnamese [10], Arabic [11], and Australian versions [12].…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…The result of test-retest analyses showed that the MCKD-SM was very stable over the 2-week period. Besides, ICC score was higher than the original [9], Vietnamese [10], Arabic [11], and Australian versions [12].…”
Section: Discussionmentioning
confidence: 71%
“…Similar to the original (α = 0.77-0.92) [9], Vietnamese (α = 0.77-0.90) [10], Arabic (α = 0.71-0.83) [11], and Australian (α = 0.72-0.85) [12] versions, Cronbach's α for all factors in MCKD-SM are reasonably high and reliable to measure self-management behaviour in the Malay-speaking population. The result of test-retest analyses showed that the MCKD-SM was very stable over the 2-week period.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Both instruments were translated into Arabic using the backward translation technique and validated in patients with CKD [ 31 ]. The internal consistency of the Arabic version of the KiKS and CKD-SM-29 was 0.75 and 0.91, respectively.…”
Section: Methodsmentioning
confidence: 99%